PERAN KEPUASAN KONSUMEN MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN (STUDI PADA KONSUMEN TEH GELAS DI KOTA DENPASAR) - Arya Dwi Putri, Kadek Ayu Anggi; Rastini, Ni Made (E-Jurnal Manajemen, 2022)
The competition for packaged tea drinks has developed rapidly due to changes in people's lifestyles in consuming tea. This study aims to analyze the role of consumer satisfaction in mediating the effect of product quality on customer loyalty. The research location is Denpasar City with an unlimited population. The sample was determined by purposive sampling and 100 people were taken. Data was collected using a survey approach and the instrument of this research was a questionnaire which was measured using a Likert scale. Data analysis was performed using path analysis. The results showed that product quality and customer satisfaction had a positive and significant effect on customer loyalty, product quality had a positive and significant effect on consumer satisfaction. consumer goals mediate the effect of product quality on customer loyalty Teh Gelas. The implications of this research theoretically support the findings of previous studies and studies related to customer loyalty. The practical implication for the Parents Group is to maintain product quality in order to create satisfaction for consumers and ultimately lead to a sense of consumer loyalty to the product. Keywords : Product Quality, Customer, Customer Loyalty